2021
DOI: 10.3390/atmos12020278
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the WRF Temperature and Precipitation Performance Sensitivity to Spatial Resolution over Central Europe

Abstract: The grid size resolution effect on the annual and seasonal simulated mean, maximum and minimum daily temperatures and precipitation is assessed using the Advanced Research Weather Research and Forecasting model (ARW-WRF, hereafter WRF) that dynamically downscales the National Centers for Environmental Prediction’s final (NCEP FNL) Operational Global Analysis data. Simulations were conducted over central Europe for the year 2015 using 36, 12 and 4 km grid resolutions. Evaluation is done using daily E-OBS data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…(2019) for North America and Stergiou et al. (2021) for Central Europe and cannot be associated with a single variable. They can be the result of synoptic conditions, feedback processes and parameterizations.…”
Section: Resultsmentioning
confidence: 99%
“…(2019) for North America and Stergiou et al. (2021) for Central Europe and cannot be associated with a single variable. They can be the result of synoptic conditions, feedback processes and parameterizations.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the inadequate horizontal resolution of the model in this study may also contribute to discrepancies between the simulated and observed precipitation. Higher horizontal resolution enables the WRF model to simulate small-scale precipitation systems better, thereby aiding in a more accurate representation of precipitation distribution, intensity, and spatiotemporal variations [55,56]. Note that the IMERG Final Run products have also been compared with ground-based observations and other satellite precipitation products; we found that there also exists a significant discrepancy in the rainfall amount among different precipitation products (not shown), which could affect the magnitude of the difference between observation and WRF simulated precipitation.…”
Section: Limitations Of the Researchmentioning
confidence: 99%
“…When computer constraints prevent high resolution grids from covering a whole domain, this option is employed. The coarse resolution grids are referred to as parents, whereas the fine resolution grids are referred to as nests [13]. The advantage of the ARW's nesting infrastructure over approaches used in other models is the efficient execution of nested simulations on concurrent distributed-memory computer systems.…”
Section: Introductionmentioning
confidence: 99%
“…One-way nesting occurs when information from the coarse grid is transferred to the finer grid. Two-way nesting when the coarse grid's information is supplied to the finer grid, and the finer grid's outcome substitutes the coarse grid's outcome at points within the fine grid [13]. many studies have used numerical weather models to address various phenomena in Iraq.…”
Section: Introductionmentioning
confidence: 99%